Environmental risk factors for temporal lobe epilepsy – Is prenatal exposure to the marine algal neurotoxin domoic acid a potentially preventable cause? - Stewart, Ian (Medical hypotheses, 2010)
Temporal lobe epilepsy with hippocampal sclerosis (TLE-HS) is one of the more common forms of chronic epilepsy. Its aetiology is unknown, though an early developmental insult is thought by some to be an important trigger. There is not a strong genetic predisposition; gene–environment interactions are more significant considerations. Environmental risk factors for TLE-HS are under-researched. Domoic acid (DA) is an environmental neurotoxin of algal origin that can contaminate marine food webs. DA can cross the placenta, is significantly more toxic to the developing brain compared to the adult brain, and has affected humans and marine wildlife through mass poisonings. DA coincidentally has a decades-long history of use as a chemical model of temporal lobe epilepsy, along with its close structural analogue kainic acid (also of algal origin). The principal hypothesis presented here is that dietary exposure to doses of DA that are sub-clinical in pregnant women may be sufficient to damage the foetal hippocampus and initiate epileptogenesis. The hypothesis could be tested both experimentally by in vivo proof-of-concept animal studies that expand on current knowledge of prenatal susceptibility to DA neurotoxicity, and by epidemiological investigations directed towards dietary exposure to marine food products. If only a small proportion of the attributable risk for TLE-HS is found to be due to gestational exposure to DA, the public health implications would still be of great significance, as this would represent a potentially preventable exposure. Other potent neurotoxins are produced by marine microalgae and freshwater cyanobacteria. These structurally and mechanistically diverse toxins can also contaminate water supplies, seafood and shellfish. Several operate by modulating ion channels, so may also be of interest to epilepsy researchers. DA is also the subject of preliminary scrutiny in strandings involving odontocete cetaceans. The implications of such work are discussed here.